AUTONOMOUS POWER SUPPLY SYSTEMS WITH RENEWABLE SOURCES OF ENERGY AND SMART GRID - L. M. Chetoshnikova; N. I. Smolentsev; S. A. Chetoshnikov; G. V. Gusarov (Известия высших учебных заведений: Проблемы энергетики)
The use of modern devices and technologies in power supply systems will provide consumers with high-quality energy. Especially effective in this direction will be the construction of autonomous systems using renewable energy sources and local smart grids. The coordinated work of all elements of systems and optimal control of energy flows is solved by mathematical modeling methods.